Liver transplantation in the United States during the COVID‐19 pandemic: National and center‐level responses. Issue 5 (10th November 2020) - Strauss, Alexandra T.; Boyarsky, Brian J.; Garonzik‐Wang, Jacqueline M.; Werbel, William; Durand, Christine M.; Avery, Robin K.; Jackson, Kyle R.; Kernodle, Amber B.; Baker, Talia; Snyder, Jon; Segev, Dorry L.; Massie, Allan B.
Abstract : COVID‐19 has profoundly affected the American health care system; its effect on the liver transplant (LT) waitlist based on COVID‐19 incidence has not been characterized. Using SRTR data, we compared observed LT waitlist registrations, waitlist mortality, deceased donor LTs (DDLT), and living donor LTs (LDLT) 3/15/2020‐8/31/2020 to expected values based on historical trends 1/2016‐1/2020, stratified by statewide COVID‐19 incidence. Overall, from 3/15 to 4/30, new listings were 11% fewer than expected (IRR = 0.84 0.890.93 ), LDLTs were 49% fewer (IRR = 0.37 0.510.72 ), and DDLTs were 9% fewer (IRR = 0.85 0.910.97 ). In May, new listings were 21% fewer (IRR = 0.74 0.790.84 ), LDLTs were 42% fewer (IRR = 0.39 0.580.85 ) and DDLTs were 13% more (IRR = 1.07 1.151.23 ). Centers in states with the highest incidence 3/15‐4/30 had 59% more waitlist deaths (IRR = 1.09 1.592.32 ) and 34% fewer DDLTs (IRR = 0.50 0.660.86 ). By August, waitlist outcomes were occurring at expected rates, except for DDLT (13% more across all incidences). While the early COVID‐affected states endured major transplant practice changes, later in the pandemic the newly COVID‐affected areas were not impacted to the same extent. These results speak to the adaptability of the transplant community in addressing the pandemic and applying new knowledge to patient care. Abstract : This registry‐based study of liver transplantation in the United States describes the substantial impact of the COVID‐19 pandemic on waitlist events over time and highlights the resiliency of the transplant community.